Changes in the castilian dialect and communication distances in university students. A study of psycholinguistic skills and bilingualism in Peru - Canales G., Ricardo (2015)
The study sought to determine if differences exist psycholinguistic and communication among university students, given their different linguistic and sociocultural reality. 20 students of Greater National University of San Marcos (Castilian dialect of coastal riverine), 18 students of the National University San Agustin de Arequipa (Castilian southern Andes) and 28 students of the National University of Huancavelica (Quechua Castilian interlectal condition) was examined ). The brief bilingual Test (González 2006) and experimental psycholinguistic tests was used: auditory perception, lexical processes, semantic and pragmatic processes, both in understanding and oral production. The results showed differences in most dimensions of oral language: comprehension (speech perception, word recognition, syntactic and semantic domain) and production (object recognition, semantic fluency, syntactic and pragmatic domain) for the group at the expense of Lima students mainly from Huancavelica (Quechua Castilian interlectal condition). This difference in psycholinguistic processes, manifests itself in a deficit in communication processes.